2010
DOI: 10.1002/etc.317
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of current‐use and organochlorine pesticides in crab embryos from northern California, USA

Abstract: Invertebrates have long been used as resident sentinels for assessing ecosystem health and productivity. The shore crabs, Hemigrapsus oregonensis and Pachygrapsus crassipes, are abundant in estuaries and beaches throughout northern California, USA and have been used as indicators of habitat conditions in several salt marshes. The overall objectives of the present study were to conduct a lab-based study to test the accumulation of current-use pesticides, validate the analytical method and to analyze field-colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 33 publications
(42 reference statements)
1
13
0
Order By: Relevance
“…However, the average lipid-basis concentration of ∑DDT in loaches (418.89 ng g −1 ) was higher by 2.2 times than that in mitten-handed crabs (137.70 ng g −1 ). Compared with published data, the total DDT concentrations in mitten-handed crabs from this study were comparable to those (mean, 12.8 ng g −1 ww) in sea crabs (Scylla serrata and Ovalipes punctatus) collected from South China [25], but were less than those in river crabs (526−821 ng g −1 lw) collected from Qiangtang River of China [26], and also less than those in most of sand crabs (43-13000 ng g −1 lw) along the California coast [20,27,28]. Moreover, the total DDT contents in loaches determined in this study were found to be less than those (125−127 ng g −1 ww) in rice field eel (Monopterus albus) obtained from Hong Kong markets [29].…”
Section: Bioaccumulation Of Organochlorine Pesticidessupporting
confidence: 53%
See 1 more Smart Citation
“…However, the average lipid-basis concentration of ∑DDT in loaches (418.89 ng g −1 ) was higher by 2.2 times than that in mitten-handed crabs (137.70 ng g −1 ). Compared with published data, the total DDT concentrations in mitten-handed crabs from this study were comparable to those (mean, 12.8 ng g −1 ww) in sea crabs (Scylla serrata and Ovalipes punctatus) collected from South China [25], but were less than those in river crabs (526−821 ng g −1 lw) collected from Qiangtang River of China [26], and also less than those in most of sand crabs (43-13000 ng g −1 lw) along the California coast [20,27,28]. Moreover, the total DDT contents in loaches determined in this study were found to be less than those (125−127 ng g −1 ww) in rice field eel (Monopterus albus) obtained from Hong Kong markets [29].…”
Section: Bioaccumulation Of Organochlorine Pesticidessupporting
confidence: 53%
“…Mitten-handed crab and loach both have the habit to dig deep burrows in the mud, and thus they have the higher potential to accumulate the hydrophobic organic pollutants from the mud. Several studies indicated the site specific bioaccumulation of organochlorine pesticides and PCBs in crab, and suggested crab embryo as a good indicator of ecosystem health [19,20]. Therefore, a great concern should be paid to the health risk of consuming mitten-handed crab and loach cultivated in rice field.…”
mentioning
confidence: 99%
“…For example, Bodega Harbor is a tidally flushed estuary that experiences negligible freshwater runoff during summer and fall but substantial runoff events during winter and spring. In particularly rainy winters, Petrolisthes cinctipes in Bodega Harbor is exposed to greater volumes of freshwater runoff as well as increased concentrations of pollutants, such as fertilizers, pesticides, herbicides, and automobile fluids (Smalling et al 2010). Freshwater runoff and pollutants may strongly affect the trace element signature of water masses and embryos in Bodega Harbor in a wet year, such as 2006 (124.5 cm rainfall), whereas the signature would be more heavily influenced by the influx of seawater during a dry year, such as 2008 (72.4 cm rainfall; data collected by the Bodega Ocean Observing Node at 38°19.110' N, 123°04.294' W; http:// bml.…”
Section: Discussionmentioning
confidence: 99%
“…We created a site atlas for the porcelain crab Petrolisthes cinctipes because crabs are excellent candidates for trace-element studies. Embryos are brooded externally and incorporate trace elements from substrates as well as surrounding waters, resulting in distinctive signatures (Anderson et al 2006, Smalling et al 2010.…”
Section: Introductionmentioning
confidence: 99%
“…This species is an excellent candidate for trace element studies because (1) embryos are brooded externally and take up trace elements from substrates as well as surrounding waters (Anderson et al 2006, Smalling et al 2010, resulting in distinctive signatures along the open coast of northern California, USA , and (2) larvae molt through only 2 larval stages before metamorphosing to postlarvae after approximately 42 d (Shanks & Eckert 2005). In this study, we (1) collected embryos from sites with distinctive trace element signatures and reared larvae in seawater from a common source in the laboratory; (2) extracted and analyzed soft tissues from each developmental stage; and (3) compared elemental signatures from the larval and postlarval stages to the embryos obtained from each site.…”
Section: Introductionmentioning
confidence: 99%